EVOLUTIVE FEATURES OF CHOLANGIOCARCINOMA - Andra Teodor; Dănuț Teodor; Cătălina Luca; Gabriela Jugănariu; Laura Ghibu; Codrina Bejan; Carmen Dorobăț (Romanian Society of Oral Rehabilitation, 2014)
Cholangiocarcinoma is a rare disease, accounting for less than 2% of all human malignancies. We present two cases of cholangicarcinoma admitted to the Infectious Diseases Hospital for postoperative infectious complications. One case presented cholangitis following biliary stent placement associated with multiple liver abscesses requiring percutaneous transhepatic biliary drainage. Bacteriological analysis identified at separated exams: carbapenem-resistant and colistin-susceptible Acinetobacter (blood and bile cultures), carbapenem- and fluoroquinolone-resistant Klebsiella pneumoniae (bile culture), colistin and antipseudomonal beta-lactam agents resistance Pseudomonas aeruginosa (secretion from liver abscess), and ciprofloxacin- resistant Escherichia coli (secretion from liver abscess, bile culture). The second case presented cholangitis on following external biliary drainage. At repeated hospitalizations the bile cultures showed: ciprofloxacin-sensitive Enterobacter and Escherichia coli, vancomycin-sensitive Enterococcus, Candida. Conclusions: Cholangiocarcinoma remains one of the most difficult tumors in terms of radical surgical treatment. There is a relationship between biliary stents, colonized bile, and postoperative infections. The etiology of the analyzed postoperative complications is dominated by the presence of Gram negative bacilli. The analysis of bacterial susceptibility to antimicrobials confirms the current problem of carbapenem and ciprofloxacin resistance, colisin remaining the proper therapeutic option.